MORPHOLOGICAL, BIOCHEMICAL AND GENETIC CHARACTERIZATION OF CITRUS CANKER PATHOGEN (XANTHOMONASAXONOPODIS) FROM CITRUS CULTIVARS OF PUNJAB, PAKISTAN - I. Shehzadi1and S. Naz (Journal of Animal and Plant Sciences, 2019)
The objective of the present study was to identify citrus canker pathogen (Xanthomonas axonopodis) and disease severity among different citrus cultivars collected from citrus growing area (CRI) of Punjab, Pakistan. Morphological, biochemical and molecular markers characterized the pathogen. Total 95 samples were collected from grapefruit (C. paradis), kumquats (C. japonica) and lemon and limes (C. limon) and subjected to biochemical analysis by API strip. Three different primer sets targeting 16SrDNA and internally transcribed spacer region (ITS) were used to check genetic variability by PCR. The infectious pathogen colonies were found to be small, yellow, mucoid and gram negative by gram staining. The oxidase, urease tests were negative and casesin hydrolysis, citrate utilization, methyl red test, catalase tests were positive for the pathogen via API strips. All the collected samples were positive for the disease by PCR and the disease severity was also measured by percentage mean. The highest disease severity (82%) was observed in grapefruits followed by lemon and limes (70%) while the lowest (30%) was in kumquats. The present results revealed that citrus cultivars have variability towards the susceptibility of citrus canker and phylogenetic analysis revealed that A type citrus canker is prevalent in selected region of Pakistan.
Keywords: citrus canker; biochemical tests; Xanthomonas axonopodis; Biochemical assay; PCR